Proportional Predictive Control of Networked Linear Switched Reluctance Machine System With Time-Varying Delay - Qiu, Li; Deng, Tao; Yang, Xiaomei; Najariyan, Marzieh; Pan, Jianfei; Liu, Chengxiang (Frontiers in Control Engineering, 2022)
In this paper, a proportional predictive (PP) control strategy is proposed and high precision position tracking controller is designed for the networked linear switched reluctance machine system (NLSRMS) with time-varying delay. The closed-loop system model of the NLSRMS is constructed based on the PP control strategy. The stability conditions of the system are proposed by combining the optimal control value calculated by the cost function. The controller of the closed-loop NLSRMS is designed by using continuously updated predictive output equation information based on calculation. The comparative study of the proposed PP and PID control methods is presented by tracking several types of signal. The maximum steady errors of PP and PID control strategies are 0.2 mm and 2 mm under the sinusoidal signal, respectively. The maximum steady errors of PP and PID control strategies are 0.07 mm and 0.7 mm under the square signal, respectively. The simulation results show the effectiveness of the proposed PP control strategy.